UPAYA INDONESIA DALAM MENINGKATKAN EKSPOR PRODUK INDUSTRI MAKANAN DAN MINUMAN KE KOREA SELATAN TAHUN 2014-2019 - Metrina Veni; Umi O. Retnaningsih (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
The food and beverage industry is one of 5 sectors focused on development by the Indonesian government, because it has a big influence on the country's economic growth. So the food and beverage industry is included in